Ciudadanos pobres y mercados de consumo en la ciudad de Huánuco 2010-2013 - Lovon Rondon, Ortiz (2017)
The city of Huanuco in the last 50 years had a significant growth, having a population of 11,996 in 1940 went on to have a population of 149.210 inhabitants in 2007, in that period grew by more than 12 times. Physically comprises the districts of Huanuco, Amarilis and Pillco Brand. Its strategic location in the central eastern region of the country allowed to be a center of attraction for general trade and foreign-owned supermarkets as: Plaza Vea, Metro and others. In the present work tries to identify the factors that led to the operation of supermarkets and identify patterns and practices of consumption of the various sectors of the urban population of Huanuco.